Uso Não Financeiro de Blockchain: Um Estudo de Caso Sobre o Registro, Autenticação e Preservação de Documentos Digitais Acadêmicos - Costa, Rostand; Faustino, Daniel; Lemos, Guido; Queiroga, Ademir; Djohnnatha, Cláudio; Alves, Felipe; Lira, Jordan; Pires, Mateus (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain), 2018)
The purpose of this paper is to to investigate the potential use of the blockchain technology combined with active distributed repositories to create a platform, scalable and agnostic1, specialized in the authentication and preservation of digital documents. As a proof of concept of the proposed platform, was performed the construction of a public service for digital registration and verification of the authenticity of academic documents. The prototype of the service offers an interface for educational institutions to register official documents, such as diplomas and certificates, using blockchain and an interface so that users can verify the authenticity of a document through its registration number in a DLT. The documents registered in the service are automatically inserted in the long-term digital preservation repository.